Administration of an adeno-associated viral vector expressing interferon-β in patients with inflammatory hand arthritis, results of a phase I/II study. Issue 1 (January 2022) - Vrouwe, J.P.M.; Meulenberg, J.J.M.; Klarenbeek, N.B.; Navas-Cañete, A.; Reijnierse, M.; Ruiterkamp, G.; Bevaart, L.; Lamers, R.J.; Kloppenburg, M.; Nelissen, R.G.H.H.; Huizinga, T.W.J.; Burggraaf, J.; et al.
Summary: Objective: Inflammatory hand arthritis (IHA) results in impaired function. Local gene therapy with ART-I02, a recombinant adeno-associated virus (AAV) serotype 5 vector expressing interferon (IFN)-β, under the transcriptional control of nuclear factor κ-B responsive promoter, was preclinically shown to have favorable effects. This study aimed to investigate the safety and tolerability of local gene therapy with ART-I02 in patients with IHA. Methods: In this first-in-human, dose-escalating, cohort study, 12 IHA patients were to receive a single intra-articular (IA) injection of ART-I02 ranging 0.3 × 10 12 -1.2 × 10 13 genome copies in an affected hand joint. Adverse events (AEs), routine safety laboratory and the clinical course of disease were periodically evaluated. Baseline- and follow-up contrast enhanced magnetic resonance images (MRIs), shedding of viral vectors in bodily fluids, and AAV5 and IFN-β immune responses were evaluated. A data review committee provided safety recommendations. Results: Four patients were enrolled. Long-lasting local AEs were observed in 3 patients upon IA injection of ART-I02. The AEs were moderate in severity and could be treated conservative. Given the duration of the AEs and their possible or probable relation to ART-I02, no additional patients were enrolled. No systemic treatment emergent AEs were observed. The MRIs reflected the AEs by (peri)arthritis. No T-cell response against AAV5 or IFN-β, nor IFN-β antibodies could be detected. Neutralizing antibody titers against AAV5 raised post-dose. Conclusion: Single IA doses of 0.6 × 10 12 or 1.2 × 10 12 ART-I02 vector genomes were administered without systemic side effects or serious AEs. However, local tolerability was insufficient for continuation. Trial registration: NCT02727764.